Ideology and truth : the return of the old couple in the post-truth era - Petković, Krešimir, politolog (Array, 2019)
The author argues that any discourse analysis, as well as other approaches in social sciences and humanities, cannot ultimately avoid the truth and ideology distinction. The first part of the article provides several glimpses at the Western philosophical tradition that preserves the value of truth. In the second part, an idea for political science, grounded in such a history of ideas, is sketched. After a brief discussion of what is ideology as opposed to truth, the author proposes a thesis about ideology, identity and power, and several heuristic ideas how to develop it. In the third part, he briefly provides examples from political and policy analysis that correspond to such a project. In the final part, he explains the importance of preserving the distinction between ideology and truth in the discursively postulated “post-truth” era. This combination of epistemology, science, analysis and teleology is reflected together in one political area of utmost importance for political science operating in the public sphere: the politics of naming.